Analysis of the Influence of Transformational Leadership Style on Employee Performance at Bank Syariah Indonesia Sub-Branch Office Juanda Medan - Rudi Hadian Siregar; M. Ilham Pratama; Isdarmanto Isdarmanto; Andrea Dimitri Nasution; Rohman Rohman (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyze the influence of transformational leadership style on employee performance at Bank Syariah Indonesia, Juanda Sub-Branch Office Medan. The research method used a quantitative approach with a sample of 31 employees taken through total sampling technique. Data collection was carried out using a questionnaire with a Likert scale. Data analysis used simple linear regression with the help of the SPSS program. The results showed that transformational leadership style had a positive and significant effect on employee performance. This is evidenced by the regression coefficient value of 0.690 and a significance value of 0.000 < 0.05. The magnitude of the influence of transformational leadership style on employee performance reached 84.2% as indicated by the R Square value of 0.842. The conclusion of this study is that the better the implementation of transformational leadership style, the higher the employee performance at Bank Syariah Indonesia KCP Juanda Medan.